Anesthetized guinea pig as a model for drug testing - Bartakova, A; Novakova, M; Stracina, T (Physiological research, 2022)
Based on the World Health Organization statistics, cardiovascular diseases represent the major cause of death worldwide. Although a wide range of treatment approaches and pharmaceuticals is available, the therapy is often not effective enough and therefore health risks for the patient persist. Thus, it is still essential to test new drug candidates for the treatment of various pathophysiological conditions related to cardiovascular system. In vivo models represent indispensable part of preclinical testing of such substances. Anesthetized guinea pig as a whole-body model allows to evaluate complex reactions of cardiovascular system to tested substance. Moreover, action potential of guinea pig cardiomyocyte is quite comparable to that of human. Hence, the results from this model are then quite well translatable to clinical medicine. Aim of this paper was to summarize the methodology of this model, including its advantages and/or limitations and risks, based on the effects of two substances with adrenergic activity on the ECG parameters. The model of anesthetized guinea pig proved to be valuable and suitable for testing of drugs with cardiovascular effects.
Keywords: elektrokardiografie; kardiovaskulární systém; krevní tlak; Myocardial Contraction; Guinea Pigs; Disease Models, Animal; Cardiovascular System; Heart Rate; morčata; srdeční frekvence; Electrocardiography; modely nemocí na zvířatech; preklinické hodnocení léčiv; zvířata; Humans; Blood Pressure; Heart; Drug Evaluation, Preclinical; kontrakce myokardu; srdce; lidé; Animals